2015
DOI: 10.1093/bfgp/elv042
|View full text |Cite
|
Sign up to set email alerts
|

Mutant power: using mutant allele collections for yeast functional genomics

Abstract: The budding yeast has long served as a model eukaryote for the functional genomic analysis of highly conserved signaling pathways, cellular processes and mechanisms underlying human disease. The collection of reagents available for genomics in yeast is extensive, encompassing a growing diversity of mutant collections beyond gene deletion sets in the standard wild-type S288C genetic background. We review here three main types of mutant allele collections: transposon mutagen collections, essential gene collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…This study initially examined the gene-drug interactions of Undaria pinnatifida fucoidan ( UPF ) by screening the complete S. cerevisiae gene deletion library to achieve an unbiased genome-wide assessment of the eukaryotic genetic/functional pathways potentially affected by this fucoidan. Especially in cases where (i) a test compound is associated with a multitude of biological effects, or (ii) nothing is known about the biological effects of a test compound, or (iii) a gene of interest, this approach has been used successfully [28]. The present study identified a large number of interacting pathways affected by UPF that broadly affected cellular energy metabolism, RNA synthesis, DNA synthesis and repair, cell cycle control, protein synthesis and transport.…”
Section: Discussionmentioning
confidence: 99%
“…This study initially examined the gene-drug interactions of Undaria pinnatifida fucoidan ( UPF ) by screening the complete S. cerevisiae gene deletion library to achieve an unbiased genome-wide assessment of the eukaryotic genetic/functional pathways potentially affected by this fucoidan. Especially in cases where (i) a test compound is associated with a multitude of biological effects, or (ii) nothing is known about the biological effects of a test compound, or (iii) a gene of interest, this approach has been used successfully [28]. The present study identified a large number of interacting pathways affected by UPF that broadly affected cellular energy metabolism, RNA synthesis, DNA synthesis and repair, cell cycle control, protein synthesis and transport.…”
Section: Discussionmentioning
confidence: 99%
“…One of the drawbacks preventing wide-scale application of TEs in gene manipulation is that the mechanisms and scope of how they affect gene and genome function are not always well understood. Additionally, biases in transposition targeting and insertions can result in an uneven distribution of insertions over the fungal genome [110]. For example, transposable element Tf1 preferentially targets promoters of genes induced by environmental stresses.…”
Section: Transposable Elementsmentioning
confidence: 99%
“…These functional genomic approaches leverage genome‐wide diversity generated by laboratory manipulation and/or leveraging the natural strain genetic diversity followed by screening or selection for the desired trait such as product tolerance. Collections of yeast mutants have been extensively studied to describe gene and proteins function and has contributed much to the field of functional genomics (Nislow, Wong, Lee, & Giaever, ; Norman & Kumar, ). One of the limitations of those collections is that they rely solely on the genetic backgrounds of lab strains and as we discuss in this review; strains used in industrial process are not derivatives of lab strains.…”
Section: Leveraging Genome‐scale Diversity For Host Optimizationmentioning
confidence: 99%